RANCANG BANGUN APLIKASI MONITORING PENCADANGAN DAYA LISTRIK DENGAN MEMANFAATKAN TENAGA KINCIR ANGIN - Meilia Nur Indah Susanti (PETIR, 2015)
Wind power plant is a power plant that uses wind as an energy source to produce electricalenergy. This generator can convert wind energy into electrical energy using a wind turbine orwindmill. Power generation system using wind as an energy source is an alternative system that isgrowing rapidly, considering wind energy is one that is not limited in nature.Computer technology is a part of human life and society today, even basically technology ingeneral and computers in particular is one of the primary means for people to improve their qualityof life. Technological developments lately running so fast, and computer technology including veryfast reaching up in almost all aspects of life so that eras experts now call it the computerized era.Computer technology can be used for field electrical one of them to do the monitoring.Computer engineering includes system design hardware and computer programs. Where the latterelectrical energy generated from the wind before being used will be stored in advance in thebattery, in this research by using application monitoring to determine how much current is enteredby using the current sensor and a voltage sensor to determine the current out using arduino.